Identifikasi dan Penetapan Kadar Rhodamin B pada Eye Shadow secara Kromatografi Lapis Tipis dan Spektrofotometri Ultraviolet-Visible - Siva Fauziah; Dede Komarudin; Citra Dewi (STIKIM Press, 2020)
Abstract Based on BPOM findings in 2016 there is still the presence of Rhodamin B which is used as one of the dyes in cosmetics. It causes irritation to the skin, respiratory tract and is carcinogenic. The purpose of this study to conduct an examination and determination of Rhodamin B in eye shadow in the Kalideres traditional market. The sample used for the research is eye shadow that is bought from cosmetics stores and cosmetic kiosks, which circulated in the Kalideres traditional market. The sample consist of five different brands based on three criteria is eye shadow which does not include the ingredients used, the writing in the packaging used a language other than Indonesia and does not have a permit number from BPOM. This research was conducted to identify the presence of Rhodamin B in eye shadow with KLT method ( thin layer chromatography), the eluent used is N-butanol, etil asetat, amoniac 25% (10 : 4 : 5) then detected with UV light 254 nm and determination of the content using UV-Vis spectrophotometry method at maximum wavelength 553 nm using as blank is methanol. The resulted was presence of Rhodamine B in sample code A and sample code D with the average value of Rhodamine B levels in the sample examined, the sample code A is 1,3063 mg/g and sample code D is 1,2564 mg/g. Keywords: Rhodamine B, Eye Shadow, KLT, Uv-Vis Spectrophotometry